Review Of "Chasing Resistance: New Antibiotics For A Changing Landscape - Eman Hamza Mohammed (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Antimicrobial resistance (AMR) is an age-old biological phenomenon, as evidenced by its evolutionary history and abundance of environmental immunity Antibiotics used by humans contributes to resistance to acquired disease, a public health issue that drives the selection of resistance genes. A.M.R. One of the most important strategies to combat AMR is the search for new antibiotics. During the 1980s, existing products were either enhanced or modified in antibiotics currently on the market. The World Health Organization (WHO) warns of limited new candidates and highly characterizes the current pipeline. After careful analysis of preclinical and therapeutic pipelines, it seems expected that very few new antibiotics will enter the market in the coming years . Most of these candidates do not meet the new standards required to adequately address the growing threat of antimicrobial resistance (AMR).The key principles to cope with the rapidly emerging AMR are diversity and innovation which are done. R&D efforts should address new antibiotic resistance. Although there is promising potential to change the dynamics between the spread of AMR, antibiotic reserves, and meeting new lead standards, we examine the historical context and challenges associated with drug a kills bacteria detection, and various other processes. Let us describe the proposed methods of revitalizing the pipeline.